Performance Evaluation of T-Shaped Noise Barriers Covered with Oblique Diffusers Using Boundary Element Method - MONAZZAM, Mohammad Reza; ABBASI, Milad; YAZDANIRAD, Saeid (Archives of Acoustics, 2019)
One of the most effective designs to control the road traffic noise is the T-shaped barrier. The aim of this study was to examine the performance of T-shape noise barriers covered with oblique diffusers using boundary element method. A 2D simulation technique based on the boundary element method (BEM) was used to compute the insertion loss at the center frequency of each one-third octave band. In designed barriers, the top surface of the T-shaped noise barriers was covered with oblique diffusers. The width and height of the barrier stem and the width of its cap were 0.3, 2.7, and 1 m, respectively. Angles of he oblique diffusers were 15, 30, and 45 degrees. The oblique diffusers were placed on the top surface with two designs including same oblique diffusers (SOD) and quadratic residue oblique diffusers (QROD). Barriers considered were made of concrete, an acoustically rigid material. The barrier with characteristics of QROD, forward direction, and sequence of angles (15, 30, and 45 degrees) had the greatest value of the overall A-weighted insertion loss equal to 18.3 to 21.8 dBA at a distance of 20 m with various heights of 0 to 6 m.